“I Was New and I Was Afraid”: The Acculturation Strategies Adopted by International First-Year Undergraduate Students in the United States - Krsmanovic, Masha (Journal of International Students, 2020)
This article utilized Berry’s acculturation model (1974, 1980, 1997) as the framework for understanding the social experiences of international first-year students in a large, public institution in the Southeast United States. Using a descriptive phenomenological research design and a sample of 10 international students, this study examined the extent to which each of the four strategies defined by the acculturation model—assimilation, integration, separation, and marginalization—emerged from the social experiences of international students during their first year of college. The results revealed that all 10 participants shared the experiences of separation, either voluntary or involuntary. For seven students in the sample, the freshman year was characterized by either willing or unwilling integration. The strategy of assimilation, both freely pursued and imposed, was reported by six students. The least evidence was recorded for the pattern of voluntary or involuntary marginalization, which emerged from the experiences of four respondents.